The Effect of Inquiry Learning and Discovery Learning on Student Learning Achievement Viewed from Spatial Intelligence - Abdul Aziz; Budiyono Budiyono; Sri Subanti (SEAMEO Regional Centre for QITEP in Mathematics, 2017)
The goal of this study is to determine the effects of inquiry learning and discovery learning upon learning achievement of junior high school students viewed from spatial intelligence. The learning models compared were inquiry learning, discovery learning, and classical model. This study used a quasi-experimental approach with a 3 x 3 factorial design. The population was all students Grade 8 of junior high school in Solo. The sample used a stratified cluster random sampling strategy which consisted of 260 students, divided into three groups, namely: 86 students in experimental group 1, 86 students in experimental group 2, and 88 students in control group. The instruments used included a mathematics achievement test and a spatial intelligence test. The data analysis used the two-way multivariate analysis of variance. The results of this study are as follows: (1) inquiry learning and discovery learning gave better learning achievement than the classical model, while inquiry learning and discovery learning resulted the same learning achievement, (2) students with high spatial intelligence had similar learning achievement with those with middle spatial intelligence, and (3) students with high and middle spatial intelligence had better learningachievement than students who had low spatial intelligence.